Nepal’s Response to Contain COVID-19 Infection - Piryani, Rano Mal; Piryani, Suneel; Shah, Jay Narayan (Journal of Nepal Health Research Council, 2020)
Nepal is a landlocked country bordering two most populous countries, India and China. Nepal shares open border with India from three sides, east, south and west. And, in north with China, where the novel coronavirus infection (CVOVID-19) began in late December 2019. The first confirmed imported case in Nepal was reported in 2nd week of January 2020. The initial response of Nepal to COVID-19 were comparably slow but country geared efforts after it was declared a ‘global pandemic’ by WHO on 11 March, 2020. Government of Nepal’s steps from 18 March, 2020 led to partial lock down and countrywide lockdown imposed on 24 March, 2020. Government devised comprehensive plan on 27 March, 2020 for quarantine for peoples who arrived in Nepal from COVID-19 affected countries. This article covers summary of global status, South Asian Association of Regional Cooperation (SAARC) status, and Nepal’s response to contain COVID-19 infection discussed under three headings: Steps taken before and after WHO declared COVID-19 a global pandemic and lab services regarding detection of COVID-19. Nepal has documented five confirmed cases of COVID-19 till the end of March 2020, first in second week of 15 January, 2020 and 2nd case 8-weeks thereafter and 3rd case two days later, 4th on 27 March and 5th on 28 March. Four more cases detected during first week of April. Non-Pharmacological interventions like social distancing and excellent personal habits are widely practiced. Country has to enhance testing and strengthen tracing, isolation and quarantine mechanism and care of COVID-19 patients as Nepal is in risk zone because of comparably weak health system and porous borders with India. The time will tell regarding further outbreak and how it will be tackled. Keywords: COVID-19; lockdown; Nepal; pandemic; response